TATA KELOLA TI PADA SISTEM INFORMASI DOSEN ITB STIKOM BALI MENGGUNAKAN FRAMEWORK COBIT 5 - Dewi, Ni Made Rai Masita (Universitas Multi Data Palembang, 2024)
ITB STIKOM Bali, as an institution of information technology education, must ensure that the implemented faculty information system is not only efficient in data management but also meets security and data integrity standards. The COBIT 5 framework, a global standard for IT governance, is used to evaluate and improve IT governance processes in the Faculty Information System at ITB STIKOM Bali. COBIT 5 provides a structured framework for managing risks, ensuring compliance, and enhancing IT performance. Understanding the importance of IT governance in the implementation of faculty information systems, institutions can ensure that information technology is optimally used to support academic and administrative activities safely, efficiently, and effectively. This research aims to identify potential improvements in the governance of the Faculty Information System. Through this research, it is hoped to provide a clear understanding of the extent to which IT governance at ITB STIKOM Bali aligns with the best practices set by COBIT 5. The results of this research are expected to serve as a basis for institutions to enhance the operational sustainability of the Faculty Information System, reduce security risks, and increase user satisfaction through the implementation of good and efficient IT governance. Therefore, good IT governance is highly necessary in managing the implementation of faculty information systems.